Pengaruh Model PjBL Berbantuan E-modul Lubuk Etnomatematika Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Umi Mardhiyah; Savitri Wanabuliandari; Henry Suryo Bintoro (Universitas Muhammadiyah Semarang, 2022)
The preliminary study at SMP Negeri 5 Pati obtained an average score of 33,44. This shows that the students' mathematical problem solving ability is still low. The purpose of this study was to test the average mathematical problem solving ability of class students who were given the Project Based Learning model assisted by the Lubuk ethnomathematics module which was better than the class with direct learning. The research method used was quantitative. Sampling with purposive sampling technique. Analysis of the data used the t-test of two independent samples. The results showed that the average mathematical problem solving ability of students who were taught the PjBL model assisted by the Lubuk ethnomathematics e-module was better than students who received direct learning. The conclusion of this study is that the PjBL model assisted by the Lubuk ethnomathematics e-module has an effect on students' mathematical problem solving abilities.